2007
DOI: 10.5194/nhess-7-141-2007
|View full text |Cite
|
Sign up to set email alerts
|

On the weak impact of the 26 December Indian Ocean tsunami on the Bangladesh coast

Abstract: Abstract. The 26 December 2004Indian Ocean tsunami damaged severely most of the Gulf of Bengal's coastal areas, but the coast of Bangladesh which stands at the edge of an extraordinarily extended continental shelf. This latter feature has been built through huge discharges of river sediments along the Brahmaputra and Ganges rivers. As a result of this enormous discharge, another interesting feature of the area is the deep underwater Canyon, connected with the estuaries, running NE-SW from 25 km off the coast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
2
17
2
2
Order By: Relevance
“…It can be observed that the island's most important effect is a delay in the arrival time, and an enhancement on wave direction change due to wave diffraction. In contrast to what was concluded by Jinadasa (2008) in Sri Lanka and Ioualalen et al (2007) in Bangladesh, the Biobio submarine canyon seems to be a tsunami natural barrier for the river mouth. They observed that submarine canyons could amplify tsunami wave amplitudes and increase inundation heights.…”
Section: Resultscontrasting
confidence: 83%
See 1 more Smart Citation
“…It can be observed that the island's most important effect is a delay in the arrival time, and an enhancement on wave direction change due to wave diffraction. In contrast to what was concluded by Jinadasa (2008) in Sri Lanka and Ioualalen et al (2007) in Bangladesh, the Biobio submarine canyon seems to be a tsunami natural barrier for the river mouth. They observed that submarine canyons could amplify tsunami wave amplitudes and increase inundation heights.…”
Section: Resultscontrasting
confidence: 83%
“…Furthermore, the effect of submarine canyons has been studied by Jinadasa (2008) and Ioualalen et al (2007), who analyzed the effect of the 2004 tsunami in Sri Lanka and Bangladeshi Coasts, respectively. They found an amplification of the wave amplitude due to the presence of the submarine canyons.…”
Section: Coastal Engineering 2012mentioning
confidence: 99%
“…Significant wave amplification also occurs along underwater canyons, like it was during the 2004 tsunami in the Indian Ocean (Ioualalen et al, 2007). In contrast to open and wide bays, the wave dynamics in such narrow geometries (the water depth and the bay width are much smaller than the wave length) has many specific features.…”
Section: Introductionmentioning
confidence: 99%
“…Such situations were observed, for instance, during the recent catastrophic tsunami at the Samoan Islands in 2009 [1,2] and in Japan in 2011 [3]. Significant wave intensification also occurs along the submarine canyons, and this was pointed out during the Indian Ocean tsunami in 2004 [4].…”
Section: Introductionmentioning
confidence: 99%